THE IMPACT OF MACROECONOMICS AND CORPORATE FUNDAMENTALS ON THE BUSINESS PERFORMANCE OF SHARIA BANKING IN INDONESIA - Oria, Hafizullah; Oria, Ehsanullah (Faculty of Islamic Economics and Business, Sultan Aji Muhammad Idris State Islamic University of Samarinda, 2025)
The aim of this research is to examine the impact of macroeconomic factors and company fundamentals on the Business Performance of Sharia banking in Indonesia. The study analysed monthly data from BI, OJK, and BPS for the years 2019-2023 using regression tests. The method used is regression analysis, with data drawn from the Sharia banking industry and macroeconomic indicators over the period from 2019 to 2023. The independent macroeconomic variables included inflation, exchange rate, and GDP, while company fundamentals were represented by FDR, CAR, BOPO, DPK, and NPF. Business Performance, as the dependent variable, was measured by Return on Assets (ROA). The results showed Indonesia experienced fluctuating economic conditions from 2019 to 2023, with low inflation and a varying exchange rate. Islamic banking in Indonesia showed strong fundamentals, with a healthy average ROA of 0.85% and a robust CAR of 16.48%; however, BOPO negatively and significantly impacts ROA, while CAR and FDR have minimal effects on ROA in Islamic banking. Inflation negatively affects ROA by increasing production costs, reducing overall banking profitability. To sustain growth, banks should focus on financing SMEs and leveraging digital technology for improved efficiency. This study focuses on the Sharia banking sector in Indonesia and incorporates both company fundamentals and macroeconomic variables. The findings will be valuable for policy-making and research in the field of Sharia banking in Indonesia.